Fabrication of Si2N2O Ceramic Foam by Combination of Direct Ink Writing and Biological Foaming Techniques. Issue 4 (9th February 2020) - Jin, Haize; Yang, Zhihua; Li, Hailiang; Jia, Dechang; Zhou, Yu
Abstract : Si2 N2 O ceramic foam is developed by the combination of biological foaming (BF) technique and direct ink writing (DIW). The effect of yeast content on the rheological properties of inks and phase composition, microstructure, and mechanical properties of ceramic foam are systematically investigated. The inks consist of different proportions of yeast suspension and ceramic start powder suspension that exhibit superior printing behavior and proper fermentation capacity. Yeast cells and additives derived from commercial active yeast are fully utilized as BF agent, nutrient, and emulsifier. The variation of yeast contents bring about the evolution of phases, pores density, and mechanical properties of ceramic parts. The Si2 N2 O foams with porosities from 61.5 ± 4.3% to 71.0 ± 4.5% are successfully fabricated. The corresponding compressive strength decreases from 33.1 ± 2.6  to 8.3 ± 1.5 MPa. As a result, a promising reference for the design and preparation of BF ceramic ink and hierarchical ceramic foam based on DIW is provided. Abstract : Si2 N2 O ceramic foam with desirable porosities (61.5 ± 4.3–71.0 ± 4.5%) and compressive strength (33.1 ± 2.6–8.3 ± 1.5 MP) is developed by the combination of biological foaming (BF) technique and direct ink writing (DIW). A promising reference for the design and preparation of BF ceramic ink and hierarchical ceramic foam based on BF and DIW is provided.